Structure and function of blueberry anthocyanins: A review of recent advances - Wenjuan Yang (Elsevier, 2022)
Blueberry anthocyanins have received increasing attention for their remarkable antioxidant, vision improvement, anti-inflammatory and cardiovascular disease prevention properties. However, the application of blueberry anthocyanins is limited due to their instability and the difficulty in absorption and utilization by the human body. This review provides a comprehensive summary of the species of blueberry (genus Vaccinium), the distribution of those species and the bioactivity of blueberry anthocyanins. Furthermore, the current review discusses the applications of blueberry anthocyanin-rich extracts, challenges in their application, and strategies to improve their bioavailability in the process of further development in the food and nutrition industry.